1989
DOI: 10.1126/science.2648574
|View full text |Cite
|
Sign up to set email alerts
|

The Pathway of Infection of Autographa californica Nuclear Polyhedrosis Virus in an Insect Host

Abstract: An immunohistochemical study was conducted to detect the temporal infection sequence of Autographa californica M nuclear polyhedrosis virus in Trichoplusia ni larvae. Staining patterns indicated that the initial infection occurred in the midgut, simultaneously in columnar epithelial and regenerative cells, but that subsequently this tissue recovered. A major envelope glycoprotein stained in a polar fashion when it was expressed in columnar epithelial cells, but not when expressed in other cells types. Systemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
180
0
8

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 273 publications
(197 citation statements)
references
References 23 publications
9
180
0
8
Order By: Relevance
“…The primary site of baculovirus infection is the columnar epithelial cells of the midgut (Kawanishi et al, 1972, Keddie et al, 1989, Volkman, 1997and Flipsen et al, 1995. Our observations on the scanning electron microscope showed that during the first hours after infection, occlusion-derived virus of AgNPV could be observed adhered to A. gemmatalis peritrophic membrane.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The primary site of baculovirus infection is the columnar epithelial cells of the midgut (Kawanishi et al, 1972, Keddie et al, 1989, Volkman, 1997and Flipsen et al, 1995. Our observations on the scanning electron microscope showed that during the first hours after infection, occlusion-derived virus of AgNPV could be observed adhered to A. gemmatalis peritrophic membrane.…”
Section: Discussionmentioning
confidence: 72%
“…that nucleocapsids could be detected in part of these cells. Several workers have shown the presence of virus particles in columnar cells of the midgut ( Kawanishi et al, 1972 andKeddie et al, 1989) early on infection. Other workers have shown, with the help of recombinant baculoviruses containing marker genes, that midgut epithelial cells support viral replication ( Volkman, 1997, Flipsen et al, 1995, Washburn et al, 1995, Knebel-Mörsdorf et al, 1996and Barret et al, 1998 and that the secondary infection was carried out by the insect tracheal system ( Engelhard et al, 1994 andBarret et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The insect midgut is a major avenue of entry into the hemocoel for pathogenic and nonpathogenic microbes (Keddie et al, 1989). Some forms of secretory PLA2, particularly the human IIA PLA2, are able to directly attack bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Host basement membrane has been identified as a potential target for improving baculovirus insecticidal efficacy (Keddie, Aponte, and Volkman, 1989). Basement membrane are extracellular sheets of protein, composed primarily of laminin, type IV collagen, and proteoglycans that surround all tissues providing structural support, and a surface for cell attachment (Rohrback and Rohrback, 1993)and (Yurchenco and O'Rear, 1993).…”
Section: Thesis Organizationmentioning
confidence: 99%
“…Occlusion-derived virus (ODV) phenotype is present within polyhedra and is responsible for primary infection of the host and horizontal transmission between insect hosts (Evans, 1986) while the budded virus (BV) phenotype is released from infected host cells and is responsible for the systemic spread of virus within the insect host. BV are also used for virus propagation in tissue culture (Entwistle and Evans, 1985;Keddie, Aponte, and Volkman, 1989).…”
Section: Baculovirus Lifecyclementioning
confidence: 99%